Broad Spectrum Antibacterial Activity of a Mixture of Isothiocyanates from Nasturtium (Tropaeoli majoris herba) and Horseradish (Armoraciae rusticanae radix) - Conrad, A.; Biehler, D.; Nobis, T.; Richter, H.; Engels, I.; Biehler, K.; Frank, U. (Drug Research, 2013)
Isothiocyanates have been reported to exert antimicrobial activity. These compounds are found in a licensed native preparation of nasturtium (Tropaeoli majoris herba) and horseradish (Armoraciae rusticanae radix) which is used for treatment of upper respiratory and urinary tract infections. The aim of our investigation was to assess the antimicrobial activity of a mixture of the contained benzyl-, allyl-, and phenylethyl- isothiocyanates against clinically important bacterial and fungal pathogens including antimicrobial resistant isolates. Susceptibility testing was performed by agar-dilution technique. Isothiocyanates were mixed in proportions identical to the licensed drug. Minimum inhibitory- and minimum bactericidal concentrations were assessed. The Minimum inhibitory concentration90 was defined as the concentration which inhibited 90% of the microbial species tested. H. influenzae, M. catarrhalis, S. marcescens, P. vulgaris, and Candida spp. were found to be highly susceptible, with minimum inhibitory concentration90 -values ranging between ≤0.0005% and 0.004% (v/v) of total ITC. Intermediate susceptibilities were observed for S. aureus, S. pyogenes, S. pneumoniae, K. pneumoniae, E. coli and P. aeruginosa, with Minimum inhibitory concentration90 -values ranging between 0.004% and 0.125% (v/v), but with elevated Minimum bactericidal concentrations90-values (2–7 dilution steps above Minimum inhibitory concentration90). Low susceptibilities were determined for viridans streptococci and enterococci. Interestingly, both resistant and non-resistant bacteria were similarly susceptible to the test preparation.
Keywords: isothiocyanate; Tropaeoli majoris herba; Armoraciae rusticanae radix; antimicrobial activity